Ischaemic necrosis of the tongue as a rare complication of cardiogenic shock. Issue 6 (2nd November 2015) - Hulstaert, E.; Roggeman, E.; Beeckman, A.-S.; Moerman, M.; Vanderstraeten, E.; Rasquin, K.; Monsaert, E.; Baert, D.; Dewint, P.; Burvenich, P.; Van Steenkiste, C.
Abstract : Ischaemic necrosis of the tongue is an unusual clinical finding. In most cases it is associated with vasculitis, particularly giant cell arteritis (GCA). Other causes include profound cardiogenic shock. We report a case of tongue necrosis in an 81-year-old Caucasian woman. The patient was admitted to the intensive care unit (ICU) for cardiogenic shock. Swelling of the tongue was reported before intubation and evolved into tongue ischaemia and necrosis of the tip of the tongue. After surgical debridement the patient recovered. To our knowledge, this is the second report of a patient surviving tongue necrosis resulting from cardiogenic shock.